Importación de cerámica plana desde Bolivia a Ecuador y su incidencia en la optimización de costos y gastos - Melendrez Vara, Anthony Rafael (2021)
The present investigation identifies the opportunity that represents for the importing sector that builders construction finishes to import flat ceramics through member or associated countries of the CAN Andean Community of Nations and thereby achieve optimization of costs and expenses, contributing to the sustainable development of the sector with quality products, accessible prices and product diversification. According to the exploratory and explanatory analysis carried out on the CONSTRUDEC company and its sub-distributors and wholesale clients, using interview and survey techniques, the openness by them to import and acquire flat ceramic products from another country of origin is identified..........